Protein carbonyl products, malondialdehyde, glutathione and vitamins C/E of breast cancer patients subjected to chemotherapy - Marisa Lucia Romani Paraboni; Jaíne Kalinoski; Bianca Genovefa Braciak; Adriana Elisa Wilk; Laura Smolski dos Santos; Elizandra Gomes Schmitt; Vanusa Manfredini; Itamar Luís Gonçalves (Brazilian Journal of Oncology)
Introduction: Various endogenous and exogenous processes contribute to the production of oxidative stress, of which anticancer drugs may be one. This study aimed at evaluating the effect of breast cancer chemotherapy on oxidative stress.